1984
DOI: 10.3758/bf03199813
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maze structure upon the performance of a multiple-goal task

Abstract: The ability of rats to find food in three kinds of mazes (radial, parallel, antiradial) was studied. Each maze had eight goalboxes. All goals were baited at the beginning of a trial, and the animal's task was to retrieve food from all eight goals. The task was divided into two phases. In the first phase, the animal was allowed access to four randomly chosen goalboxes. Once the animal had visited all four of the goals, the second phase of the trial began, in which the animal was allowed access to all eight goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A second reason for developing the ground-feeding spatial memory apparatus was that it seemed to offer more flexibility for studying pigeons' spatial working memory as a function of the spatial organization of the food sites. Studies with rats have shown that the structure of mazes can have dramatic effects on accuracy levels and response strategies (e.g., Horner, 1984). Thus, in addition to providing a general test of pigeons' working memory abilities in an open-room ground-feeding environment, the present study also provided a preliminary examination of the effect of different spatial arrangements on pigeons' choice behavior.…”
Section: Methodsmentioning
confidence: 99%
“…A second reason for developing the ground-feeding spatial memory apparatus was that it seemed to offer more flexibility for studying pigeons' spatial working memory as a function of the spatial organization of the food sites. Studies with rats have shown that the structure of mazes can have dramatic effects on accuracy levels and response strategies (e.g., Horner, 1984). Thus, in addition to providing a general test of pigeons' working memory abilities in an open-room ground-feeding environment, the present study also provided a preliminary examination of the effect of different spatial arrangements on pigeons' choice behavior.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon, termed spontaneous alternation or win-shift , has been documented in a variety of maze structures including the T maze, Y maze, and radial-arm maze. Several studies in the spontaneous alternation literature have indicated that novelty (Gaffan & Davies, 1982) and the spatial distinctiveness of the choice alternatives (Douglas, Mitchell, & Del Valle, 1974; Douglas, Mitchell, & Kentala, 1972; Horner, 1984; Schenk & Grobety, 1992) play crucial roles in spontaneous alternation behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Olton (e.g., 1978) suggested that this ability is a result of a natural “win-shift” foraging strategy, that is, a tendency for the animal to avoid recently visited food sites. This notion has generated a fair amount of criticism (e.g., Gaffan & Davies, 1981; Horner, 1984; Wilkie & Slobin, 1983) but remarkably little empirical data. One of the few relevant experiments—Olton and Schlosberg's (1978) demonstration that young rats learn “win-shift” easier than “win-stay” tasks—has been criticized for confounding task difficulty with the win versus stay conditions (Horner, 1984).…”
mentioning
confidence: 99%